2001
DOI: 10.1067/mva.2001.111978
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of occult pulmonary thromboembolism in patients with deep venous thrombosis

Abstract: Silent PTE occurred frequently in association with clots of lower limbs. The CT scan had a good availability and cost-effectiveness to detect clinically underestimated PTE. The incorporation of this exploration in the systematic diagnostic strategy of most patients with DVT to establish the extension of thromboembolic disease at diagnosis may be useful in the evaluation of added pulmonary artery symptoms and treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
17
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 39 publications
6
17
1
1
Order By: Relevance
“…This may be different from other studies and could be explained by our recruitment process: patients in Group 1 had no dyspnoea or pulmonary symptoms and those in Group 2 had positive CTPA. However, our results are in line with previous studies that have reported clinically unsuspected PE in 34-58% of patients with acute DVT, regardless of the imaging technique used [2,6,[15][16][17][22][23][24][25][26], and a prevalence of DVT in 72-82% of patients with clinically suspected/confirmed PE [1,4,27]. The relationship between the location of the upper end of the venous clot in the lower limbs and the frequency of associated PE, however, remains controversial.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This may be different from other studies and could be explained by our recruitment process: patients in Group 1 had no dyspnoea or pulmonary symptoms and those in Group 2 had positive CTPA. However, our results are in line with previous studies that have reported clinically unsuspected PE in 34-58% of patients with acute DVT, regardless of the imaging technique used [2,6,[15][16][17][22][23][24][25][26], and a prevalence of DVT in 72-82% of patients with clinically suspected/confirmed PE [1,4,27]. The relationship between the location of the upper end of the venous clot in the lower limbs and the frequency of associated PE, however, remains controversial.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, Girard et al [4] reported no relationship between the Miller score and the anatomical level of the upper end of the clot in lower limb veins. Similarly, Lopez-Beret et al [6] found that, in patients with proximal DVT (i.e. within the iliofemoral and/or femoropopliteal veins), the number of pulmonary segments affected by PE is not any higher than in patients with more distal DVT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations